Vanished! - Deary, Terry (New York : Kingfisher, 1996)
Investigates the possibility that the United States Navy during World War II conducted the Philadelphia Experiment, an experiment which rendered the battleship USS Eldridge invisible.
Keywords: United States. -- Navy -- Juvenile literature; United States. -- Navy; Eldridge (Ship) -- Juvenile literature; Eldridge (Ship); Philadelphia Experiment, 1943 -- Juvenile literature; Philadelphia Experiment, 1943.